A formal data-model of the CORBA security service. - Basin, David
We use the formal language Z to specify and analyze the security service of CORBA. In doing so, we tackle the problem of how one can apply lightweight formal methods to improve the precision and aid the analysis of a substantial, informal specification. Our approach is scenario-driven: we use representative scenarios to determine which parts of the informal specification should be formalized and then verify the formal specification against the requirements of these scenarios.
Keywords: Software; Software engineering; Requirements/Specifications.; Z; Security; Verification; CORBA security; Formal methods; Specification